Simulasi 3D Desain Cetakan Kanstin Menggunakan Finite Element Analysis - Ramdhani, Safarudin; Abror, Muhammad Fatihul; Talitha, Tita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Current developments in infrastructure development have led to tight competition in the precast concrete industry. The use of precast concrete materials supports the need for infrastructure development, especially roads and city parks, especially kanstin products. The ability of precast concrete molds depends on several factors such as design, material and manufacturing process. The aim of this research is to find out the most optimal kanstin mold design in terms of structure and service life. The Finite Element Analysis (FEA) method is used to model and analyze the performance of kanstin mold designs. Based on 3D simulations of eight geometries with WF and UNP steel frames with ASTM A36 and AISI 1081 material types, it is still within safe limits for yield strength values. The largest von mises value is for WF AISI B and the smallest for UNP AISI A. It can be concluded that the highest life cycle is for the ASTM A36 material type UNP frame thickness A with a value of 7.91 years, while the von misess stress value is 113.4 Mpa which is still below the yield strength of ASTM A36 .